2020
DOI: 10.1016/j.heliyon.2020.e05236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of educational program based on Precede-Proceed model in promoting low back pain behaviors (EPPLBP) in health care workers Shahid Beheshti University of medical sciences: randomized trial

Abstract: The PRECEDE-PROCEED model is an adaptable planning model that could be served in public health issues. The purpose of this study is to investigate the effects of an educational program based on Precede-Proceed model on promoting Low Back Pain (LBP) behaviors among health care workers (HCWs). This Double-blinded randomized trial study was conducted on 112 from 120 HCWs aged from 30 to 55 years The eligible HCWs were randomly divided to intervention group 1 (N ¼ 38), respectively intervention group 2 and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
5
15
0
1
Order By: Relevance
“…Enabling factors is one of the most important factors in increasing the skills of community health workers because without resources (standard tools) and without the use of appropriate strategies, it will be very di cult to provide self-care programs to people with pre-diabetes. In the regression study, enabling factors after self-e cacy were the most important predictors of community health workers' skills in providing self-care programs, consistent with many previous studies (23,(40)(41)(42).…”
Section: Enabling Factorssupporting
confidence: 88%
“…Enabling factors is one of the most important factors in increasing the skills of community health workers because without resources (standard tools) and without the use of appropriate strategies, it will be very di cult to provide self-care programs to people with pre-diabetes. In the regression study, enabling factors after self-e cacy were the most important predictors of community health workers' skills in providing self-care programs, consistent with many previous studies (23,(40)(41)(42).…”
Section: Enabling Factorssupporting
confidence: 88%
“…The study by Pourhaji et al [ 30 ], presented after its judgment through the ROB2: low risk of bias, and the study Yassi et al [ 25 ], presents some concerns, since it presented in D3 some concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [ 13 ] suggested that their nurse-led orthopedic pain management based on the Precede-Proceed model could help reduce pain in patients. In another study, Pourhaji et al [ 14 ] constructed a pain management model based on the Precede-Proceed model for low back pain prevention. However, there is currently no study that has tested the efficacy of the Precede-Proceed model in the pain management of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%